Acoustic power radiated into the quarter-space by a circular membrane with an asymmetric excitation - RDZANEK, Wojciech P.; RDZANEK, Witold J.; SZEMELA, Krzysztof (Archives of Acoustics, 2009)
A circular membrane excited asymmetricaly is vibrating and radiating acoustic waves into the quarter-space limited by two rigid baffles arranged perpendicularly to one another. These processes are time harmonic. The classical Neumann boundary value problem has been solved using the complete eigenfunctions system together with the corresponding coupling matrix and including the acoustic attenuation effect.